RESERVOIR MODELING AND IDENTIFIKATION BASED ON âPETROPHYSICAL ROCK TYPEâ CARBONATE RESERVOIR IN TUBAN FORMATION, APRIO FIELD, NORTHEAST JAVA BASIN - Saputra, Hendra
Aprio field located in the southern part of the North East Java Basin has produced oil from the carbonate reservoir Tuban formations and production of oil on average 2500-5000 bopd each well. Field development program in this field requires a more detailed analysis both of the characteristics to modeling of the reservoir rock properties. This tesis focused on the identification and reservoir modeling use petrophysical rock typing approach with pore geometry and structure (PGS) method. The identification of the type, composition, and distribution of rock types, can obtain comprehensive understanding of geological aspects such as diagenesis and reservoir petrophisic properties. Porosity and permeability data of the 113 core plug, which 13 have mercury injection capillary pressure (MICP) data, 48 thin sections from 3 wells, 18 wells log data, and 3D seismic is used in this study. Facies, facies association and diagenetic history analyses are performed to understand the influence of facies, depositional environments and diagenesis to the development of petrophysical rock types (PRT). Packstone with larger foram, red algae, mollusks, and corals dominate the wells that have thin section. Diagenesis occur from marine until burial stage. Secondary porosity caused by dissolution on vadose stage. By Luis Pomar, 2004, the study area has lagoon, shelf margin and upper slope fasies. PGS and petrographic analysis plays important role in the identification of rock types. On the field, there are 3 types of PRT, classified by type, size, and pore associations, (PRT 1) moldic vuggy porosity and macropore patchy association, (PRT 2) interparticle meso-macropore patchy association, (PRT 3) interparticle micropore uniform. PRT 1 and PRT 2 predominate in shelf margin fasies. PRT 3 dominate at the lagoon and upper slope fasies. Three-dimensional reservoir characterization through 3-D reservoir modeling is performed for facies, porosity and water saturation modeling. PRT and permeability modeling is controlled by PGS analysis method. Modeling results indicate a consistency between PRT distribution and petrophysical properties of the reservoir. Porosity and permeability values are high partly associated with PRT 1 and PRT 2. Reservoir quality evaluation reveals a strong relationship between the types, composition and spatial distribution of PRT and well’s productivity. The wells are dominated by PRT 1 shows a high productivity (> 4,000 bopd), the wells were dominated by PRT 1 and PRT 2 showed moderate levels of productivity (3500-4000 bopd), whereas wells that are dominated by PRT 2 only showed a low level of productivity (<3,500 bopd).